The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fendo.2013.00115
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 Deiodinase and Consumptive Hypothyroidism: A Common Mechanism for a Rare Disease

Abstract: The major product secreted by the thyroid is thyroxine (T4), whereas most of the biologically active triiodothyronine (T3) derives from the peripheral conversion of T4 into T3. The deiodinase enzymes are involved in activation and inactivation of thyroid hormones (THs). Type 1 and type 2 deiodinase (D1 and D2) convert T4 into T3 whereas D3 degrades T4 and T3 into inactive metabolites and is thus the major physiological TH inactivator. The hypothalamic-pituitary-thyroid axis maintains circulating TH levels cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…Most studies on this type of consumptive hypothyroidism report the use of levothyroxine or levothyroxine plus liothyronine for treatment [1][2][3][4][5][6][7][8][9][10][11][12]14]; while 1 study reported the use of liothyronine plus prednisolone [13]. However, there is no report of using liothyronine plus propranolol for the treatment of consumptive hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on this type of consumptive hypothyroidism report the use of levothyroxine or levothyroxine plus liothyronine for treatment [1][2][3][4][5][6][7][8][9][10][11][12]14]; while 1 study reported the use of liothyronine plus prednisolone [13]. However, there is no report of using liothyronine plus propranolol for the treatment of consumptive hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Consumptive hypothyroidism is a rare paraneoplastic syndrome that can occur in infants with hepatic haemangiomas. It results from the abnormal over‐expression of type 3 iodothyronine deiodinase (D3), a selenoenzyme responsible for inactivation of thyroid hormone molecules by converting T4 to reverse T3 (rT3), and T3 to 3,3′‐diiodothyronine (T2) . Under normal conditions, D3 regulates circulating levels of thyroid hormone and is restricted to the central nervous system, skin and some endocrine glands .…”
Section: Discussionmentioning
confidence: 99%
“…It results from the abnormal over‐expression of type 3 iodothyronine deiodinase (D3), a selenoenzyme responsible for inactivation of thyroid hormone molecules by converting T4 to reverse T3 (rT3), and T3 to 3,3′‐diiodothyronine (T2) . Under normal conditions, D3 regulates circulating levels of thyroid hormone and is restricted to the central nervous system, skin and some endocrine glands . However, biopsies have demonstrated over‐expression of D3 by hepatic haemangioma tissue …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumoral D3 activity is markedly elevated in vascular tumors, including infantile hemangioma and hemangioendothelioma in adults (Huang et al 2000, Luongo et al 2013, even to the extent of inducing clinical hypothyroidism (consumptive hypothyroidism). Opposing regulation of DIO3 or DIO1/ DIO2 expression has been reported in various human neoplasias, such as PTC, TSH tumors, BCC and colon cancer (de Souza Meyer et al 2005, Dentice et al 2007, 2012, Luongo et al 2013, Romitti et al 2016. Studies performed using 105 pituitary tumors demonstrated that D2 and D3 mRNA levels were significantly augmented in pituitary tumors compared with normal pituitary tissue.…”
Section: Intracellular Microenvironment: Deiodinase Control Over Th Smentioning
confidence: 99%